Adopting industrial designs: further IP protection for US start-ups?. Issue 2 (19th January 2023) - Power, Bernadette; Reid, Gavin C.
ABSTRACT: This article examines the determinants of adoption of industrial designs, for intellectual property (IP) protection, in a large sample of US start-ups. While patents and copyrights are widely analysed as ways of protecting proprietary knowledge in large firms, they are expensive forms of IP protection, both to create and to protect. For start-ups, cheaper and simpler methods have greater attraction, of which industrial design protection is an example. The article builds and tests an applied econometric model of industrial design adoption, using the longitudinal Kauffman Firm Survey, 2008–2012. The model is based on a microeconomic managerial utility theory of the firm, implemented within a random utility framework, leading to an estimable econometric model which takes the form of a binary probit with random effects. This model is run on an unbalanced panel sample of nearly nine thousand observations. It finds that expenditure on R&D plays a powerful role in the design adoption process. Incorporation and owner-managers' injection of equity also play a positive and significant part in design adoption. These three influences are all part of the commitment that owner-managers bring to their start-ups. Sales directed to products rather than services also have positive effects on industrial design adoption.